A construção social da oferta da carona solidária : confiança digital, aplicativos de compartilhamento e as circunstâncias de conflitos no mercado de transporte brasileiro - Costa, Karolyne Santana (2022)
The nascent Brazilian carpooling market, of the individual passenger transport (TIP) type, was built on the trust in the innovation of Uber Economy apps, which intermediate the offer of services. These new economic practices, as well as the disruption caused by their innovation models, have been investigated by different research and approaches to the Sharing Economy (CE). This thesis, first, offers a broad theoretical framework on the subject, built from the analytical-empirical method. Among the objectives, the theoretical model of sociological analysis is used, to work on the investigation of the growing classifications on these markets that are pioneers, observing how, from the proliferation of on-demand applications of Uber Economy, the formation of a new niche: carpooling in solidarity. All of this is understood as a social phenomenon built from trust in abstract systems and social sharing, knowing that these intensify when they are boosted in markets, with the advent of the Internet and Virtualization. These application markets are sustained in Brazil by many interconnected social and institutional issues. Among them are the transformations caused by ICTs (Information and Communication Technologies), which are developed together with the markets, due to the lack of regulatory processes and constitutional barriers, as well as the questions raised by Uber Economy. Conflicts and social impacts may arise from the aforementioned issues, affecting the Brazilian social and economic order. Currently, there are allegations of clandestine carpooling and unfair competition in conflict with the defenses of these cooperative practices as a solution to Brazilian social problems. Divergences and convergences were observed, from lawsuits against BlaBlaCar, another ride-hailing app, and its users.